2014
DOI: 10.1016/j.neuroimage.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Gamma band activity and the P3 reflect post-perceptual processes, not visual awareness

Abstract: A primary goal in cognitive neuroscience is to identify neural correlates of conscious perception (NCC). By contrasting conditions in which subjects are aware versus unaware of identical visual stimuli, a number of candidate NCCs have emerged, among them induced gamma band activity in the EEG and the P3 event-related potential. In most previous studies, however, the critical stimuli were always directly relevant to the subjects’ task, such that aware versus unaware contrasts may well have included differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
152
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(194 citation statements)
references
References 73 publications
25
152
5
Order By: Relevance
“…One inconsistent set of findings in the literature are a number of impressive studies that ascribe a post-perceptual locus for the P3 (Pitts, Padwal, Fennelly, Martínez, & Hillyard, 2014;Shafto & Pitts, 2015;Squires, Hillyard, & Lindsay, 1973). Our experiment though has a number of differences to these previous studies, which presumably explain the difference in findings.…”
Section: Erp Datacontrasting
confidence: 71%
See 2 more Smart Citations
“…One inconsistent set of findings in the literature are a number of impressive studies that ascribe a post-perceptual locus for the P3 (Pitts, Padwal, Fennelly, Martínez, & Hillyard, 2014;Shafto & Pitts, 2015;Squires, Hillyard, & Lindsay, 1973). Our experiment though has a number of differences to these previous studies, which presumably explain the difference in findings.…”
Section: Erp Datacontrasting
confidence: 71%
“…2) The elegant demonstration by Pitts and colleagues (Pitts, et al, 2014;Shafto & Pitts, 2015) that the P3 in their experiment was modulated by task set, does not naturally carry over to our setting. This is because task set, certainly in respect of instruction, is constant throughout our experiment.…”
Section: Erp Datamentioning
confidence: 91%
See 1 more Smart Citation
“…For one thing, magnetic stimulation of prefrontal cortex affects the voluntary control of bistable stimuli, but not passively experienced bistable stimuli [9,37]. Additionally, most frontal activity disappears when no report on sensory experience is required [38][39][40][41]. The interpretation of these data is somewhat controversial, with one group arguing that "a few null findings" should not falsify prefrontal theories of consciousness [42].…”
Section: Prefrontal Activitymentioning
confidence: 99%
“…A number of ERP studies have found enhanced P3 amplitude in relation to performing active task as opposed to passive stimulus processing (Polich, 2007). In a recent study Pitts et al, (2014) have studied P3 in relation to task relevance and visual awareness. The authors suggest that P3 reflects specific post-perceptual processes required for the execution of certain active task but not uniquely for consciously perceiving the visual stimuli.…”
Section: Theoretical Implicationsmentioning
confidence: 99%